2011
DOI: 10.1007/s10164-011-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Female mate choice based on territory quality in barn swallows

Abstract: Female mate choice based on territory quality is difficult to study because territories often contain many resources, which are difficult to quantify. Here, using the barn swallow (Hirundo rustica gutturalis) breeding at an outdoor breeding site in Japan, where each male defends only a small territory containing old nests, we studied whether females choose social mates based on territory quality. Since the territories of this species contain few other resources, territory quality can easily be assessed by quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 43 publications
1
21
1
Order By: Relevance
“…3). As expected, males with high-quality territories paired earlier, indicating female mate choice based on territory quality (Hasegawa et al 2012a; though there may still be some population differences in the relationship between territory quality and reproductive parameters; see above). Although territory quality is often related to male morphological traits (e.g., throat coloration in this species; Hasegawa et al 2014;Wilkins et al 2015), multivariable analysis indicates that territory quality is an important mate choice criteria than male morphology (in fact, effect size, Zr = 0.60, 95% CI = 0.14-1.06 for laying date and 0.62, 95% CI = 0.11-1.12 for pairing date, computed from R 2 value, is quite high for female preference for territory quality, though sample sizes were small (n = 21, 18, respectively); note that mean overall effect size for plumage ornaments was 0.21; Romano et al 2017a).…”
Section: Resources Defended or Provided By Malessupporting
confidence: 65%
See 2 more Smart Citations
“…3). As expected, males with high-quality territories paired earlier, indicating female mate choice based on territory quality (Hasegawa et al 2012a; though there may still be some population differences in the relationship between territory quality and reproductive parameters; see above). Although territory quality is often related to male morphological traits (e.g., throat coloration in this species; Hasegawa et al 2014;Wilkins et al 2015), multivariable analysis indicates that territory quality is an important mate choice criteria than male morphology (in fact, effect size, Zr = 0.60, 95% CI = 0.14-1.06 for laying date and 0.62, 95% CI = 0.11-1.12 for pairing date, computed from R 2 value, is quite high for female preference for territory quality, though sample sizes were small (n = 21, 18, respectively); note that mean overall effect size for plumage ornaments was 0.21; Romano et al 2017a).…”
Section: Resources Defended or Provided By Malessupporting
confidence: 65%
“…Although territory quality is often related to male morphological traits (e.g., throat coloration in this species; Hasegawa et al 2014;Wilkins et al 2015), multivariable analysis indicates that territory quality is an important mate choice criteria than male morphology (in fact, effect size, Zr = 0.60, 95% CI = 0.14-1.06 for laying date and 0.62, 95% CI = 0.11-1.12 for pairing date, computed from R 2 value, is quite high for female preference for territory quality, though sample sizes were small (n = 21, 18, respectively); note that mean overall effect size for plumage ornaments was 0.21; Romano et al 2017a). As swallows choose high-quality (i.e., intact) nests within their territories (Hasegawa et al 2012a) or choose colonies/breeding sites with many high-quality nests (Safran 2004(Safran , 2007; also see Ringhofer and Hasegawa 2014), it is not surprising that females choose territories with high-quality nests, though experimental validation remains to be carried out. Because territory is not the sole resource provided by males in this biparental care species, it is natural to suppose that other types of resources may also be the targets of female preference.…”
Section: Resources Defended or Provided By Malesmentioning
confidence: 94%
See 1 more Smart Citation
“…Even among European populations there is variation the strength of selection on tail length, although it remains consistently positive among populations (Møller et al 2006). Likewise, the information conveyed by these traits varies geographically, with some evidence suggesting that long tail streamers in Europe advertise indirect benefits (Møller 1994a;Møller et al 1998a); but see (Bro-Jørgensen et al 2007) for alternative explanations), whereas coloration has been suggested to advertise direct and indirect benefits in Japan (Kojima et al 2009;Hasegawa et al 2012), and could relate to both direct and indirect benefits in North America (Safran and McGraw 2004;Safran et al 2005). If the relative importance of different types of benefits varies among populations, this may result in mate choice, and consequent directional selection, on different traits, leading to phenotypic divergence and reproductive isolation based on sexually selected signals.…”
Section: Divergent Ecological and Sexual Selection In Barn Swallowsmentioning
confidence: 99%
“…Rather, among the three other adaptive reasons for infanticide (i.e., resource competition, parental manipulation, and exploitation of infants [cannibalism]; Hrdy 1974), resource competition is the most plausible explanation for the current case because the male tried to attract the female mate to the focal nest by emitting enticement calls (i.e., the focal nest is regarded as a candidate breeding nest; Turner 2006, Hasegawa et al 2013. In the sparse populations of Barn Swallows seen in Japan, in contrast with the colonial populations seen in Europe, selection pressure favoring the occupation of well-constructed nests is high to avoid high nest predation by crows (Hasegawa et al 2012; see also Fujita 1993, Suzuki 1998, reviewed in Hasegawa 2011. In fact, in contrast to European colonies, in which nests with dead nestlings generally remain for several years (Møller 2004), parents in Japanese populations often seek breeding nests and use old nests containing dead nestlings; in such cases, the dead bodies are discarded before the onset of breeding (MH, pers.…”
Section: Discussionmentioning
confidence: 92%